Doppler‐aided Global Navigation Satellite System position estimation with B‐spline smoothing strategy. Issue 3 (16th November 2021) - Sun, Jieyi; Wang, Yongqing; Shen, Yuyao
Abstract: Smoothing process can effectively improve the accuracy of the Global Navigation Satellite System (GNSS) position estimation algorithm. In this study, a Doppler‐aided GNSS position estimation algorithm with a B‐spline smoothing strategy is proposed. B‐spline signal processing is used to smoothen the code measurements with Doppler measurements, which were selected because they are more robust and immune to cycle slips than carrier phase measurements. Next, the mathematical expressions of the smoothing process and position estimation are derived. The smoothing process is based on the structure of a digital filter, which is especially suitable for real‐time applications. The Cramer–Rao lower bound of the proposed algorithm is derived. Moreover, a complete implementation structure of the proposed algorithm is presented. The validity of the proposed algorithm is verified through scenario simulation in terms of static, kinematic, and adverse environments. The advantages of the proposed algorithm are demonstrated by comparison with existing algorithms.